The production and engineering of antimicrobial peptides and their application in the coating of urinary catheters - Li, Xiang (2013)
Antimicrobial peptides (AMPs) are a promising class of molecules that can curb microbial infections without easily evoking microbial resistance. To employ AMPs as coating agents for biomedical materials and devices, obstacles which include (i) the lack of pure AMPs for detailed structure-function characterization and systematic AMP-based coating studies, as well as (ii) susceptibility of AMPs to salt need to be overcome. In this research project, human beta defensins 25 (hBD25) and 28 (hBD28) were chosen as AMP models to be studied for development into antimicrobial coating agents. hBD25 and hBD28 were discovered in the male genital tract, and thus render them very suitable peptide candidates for immobilization on urinary catheters.To produce sufficient AMPs for this research project, microbial platforms for the biosynthesis of hBD25 and hBD28 at preparative scale were developed. hBD25 was expressed predominantly as soluble aggregates despite being co-expressed with the solubility-enhancing MBP fusion tag in E. coli. This outcome necessitated the development of a refolding based bioprocess for hBD25 production, where the peptides were first subjected to denaturation-reduction, followed by an in vitro refolding step to yield bioactive hBD25 at high purity. hBD28, on the other hand, was expressed as a soluble and monomeric fusion protein, which was readily recovered at 79±5% yield and 90±2% purity using a streamlined chromatography-based bioprocess. Although both hBD25 and hBD28 completely inhibited the growth of E. coli K12 at a peptide concentration of 60 μg/ml in the absence of salt, both peptides became inactive in the presence of salt (150 mM NaCl). Given that hBD28 could be produced using a more streamlined bioprocess compared to hBD25, hBD28 was chosen as the peptide candidate for detailed engineering and structure-function characterization studies to improve its salt-resistance property. Salt intolerance of wild type hBD28 was overcome by increasing C-terminus cationicity to increase the net positive charge of the peptide. Additionally, the mutant hBD28 also exhibited improved antimicrobial potency compared to wild type hBD28 in the presence of 150 mM NaCl. Zeta potential analysis results indicate that the increased net charge of mutant hBD28 was important to overcome the salt-induced charge-shielding effect, which inhibits peptide activity in the presence of salt. Two short AMP analogs that are rich in tryptophan and positively charged amino acid residues, RK1 and RK2, were generated from the salt-resistant mutant hBD28 which exhibited excellent broad spectrum antimicrobial activity, and were used as peptide candidates for urinary catheter immobilization studies. A coupling chemistry based on covalent grafting of RK1 and RK2 on an allyl glycidyl ether (AGE) polymer brush was developed to stably immobilize the peptides on polydimethylsiloxane (PDMS) and urinary catheter surfaces. The RK1- and RK2-impregnated catheters exhibited broad spectrum biocidal and anti-biofilm activities against Gram positive bacteria, Gram negative bacteria and fungi. The mechanism of killing exhibited by these immobilized peptides was via membrane disruption, similar to that observed for their soluble counterparts, as determined by ATP leakage assay and Field Emission Scanning Electron Microscope (FESEM) analysis, but the rate of bacteria killing was observed to be lower for the immobilized peptides compared to their soluble counterparts. In conclusion, this thesis presents a proof-of-concept study on the applications of short AMPs as antimicrobial coating agents on urinary catheter surfaces. The successful development of bioprocesses allowed sufficient amounts of hBD25 and hBD28 to be produced, leading to detailed structure-activity characterization studies of these peptides. The outcome of those studies guided the rational engineering of hBD28 for salt-resistant properties, from which peptide analogs were generated for urinary catheter immobilization studies. The outcome of this thesis will pave the way for the development of other AMP-impregnated devices that combines peptide structure-function studies at both the process and molecular levels.